Oxovanádio porfirina tetrarutenada para a modificação de eletrodo e determinação simultânea de fármacos - Souza, Jonathan Augusto Matioli de (2019)
The present work describes the synthesis and characterization of tetrarutenated porphyrin oxovanadium {VO-3-TPyP[RuCl3(dppb)]4} and its use as a vitreous carbon electrode modifier for the detection of Catechol, Hydroquinone and Paracetamol drugs. The characterization of the tetrarutenated porphyrin oxovanadium was followed by the ultraviolet-visible spectrometry technique, where it can be observed its characteristic bands, which are Soret (λ = 426 nm; ε = 3.249 x 105) and Q bands α (λ = 586 nm; ε = 4,281 x 103) and β (λ = 549 nm; ε = 2,023 x 104) and by infrared spectrometry, where a moderate intensity peak of 1004 cm-1 can be observed referring to the V = O bond beyond the characteristic porphyrin peaks and phosphorus atoms in the ligand. After the modification of the vitreous carbon electrode was performed by the cyclic voltammetry technique generating an electropolymerization process, leading to the formation of the mixed valence complex {VO-3-TPyP[Ru(dppb)]4(µCl3)2}_2n^(〖8n〗^+ ) whose electrocatalytic activity was present and it was used for analyte determination. Comparing the modified and unmodified electrodes, a better response can be observed using the modified electrode, making possible to separate the anode and cathode peaks from the analytes and increase their peak currents. After the technique optimization process, a linear range of the analytes of 95-476 µmol L-1, obtaining the Limit of Detection (LD) values of 0.937; 1,596 and 1,856 µmol L-1 for the analytes Hydroquinone, Catechol and Paracetamol, respectively.